The Louisiana Purchase - Lawrence, Blythe (Expansion of our nation., 2019)
Describes the expansion of the United States, focusing on the Louisiana Purchase. Discusses the work of U.S. President Thomas Jefferson and the use of his presidential powers. Includes a quiz with answer key, a glossary, color illustrations, and further resources.